نمذجة التغيرات المستقبلية لدرجات الحرارة الصغرى بمحطة رصـــد مصراتة ( 1990-1960م) - ساسي حامد الطاهر (Al-Qurtas, 2024)
نمذجة التغيرات المستقبلية لدرجات الحرارة الصغرى بمحطة رصـــد مصراتة ( 1990-1960م)